Biodegradable polymer coated 45S5 Bioglass-derived glass-ceramic scaffolds for bone tissue engineering - Boccaccini, Aldo R.; et al. (Glass Technology, 2007)
Three-dimensional, highly porous foam-like composite scaffolds were fabricated by coating 45S5 Bioglass-derived glass-ceramic foams with a biodegradable poly-(3-hydroxybutyrate) (PHB) layer. The PHB was produced by bacteria isolation, using afermentation process. The glass-ceramic scaffolds were fabricated by the replication technique using 45S5 Bioglass powder. The sintering process was optimised in order to increase the mechanical strength of the foam scaffolds. During sintering, the glass crystallises, forming a mixed sodium calcium silicate (Na2Ca2Si3O 9) phase. The microstructure of the composite scaffolds was analysed by scanning electron microscopy and x-ray diffraction. The polymer coating did not affect the interconnectivity of the pore structure. The compressive strength of the coated and uncoated scaffolds was measured and it was found that the polymer coating considerably increased the compressive strength of the scaffolds. Bioactivity was studied by soaking the samples in a simulated body fluid (SBF) to assess the formation of hydroxy apatite (HA) crystals on the scaffolds' surfaces. It was found that these novel composite scaffolds are highly bioactive, as after two weeks of immersion in SBF, a uniform layer of HA crystals was formed. The novel Bioglass/PHB composite foams are promising candidates for bone tissue engineering scaffolds.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.biodeg